"Granny dumping": Acceptability of sacrificing the elderly in a simulated moral dilemma 1. (25th February 2014) - Kawai, Nobuyuki; Kubo, Kenta; Kubo‐Kawai, Namiko
Abstract In a simulated moral dilemma, most people would be willing to endorse killing a single individual to save five others, but do people show the same degree of resistance to sacrificing people of different ages? In the present study, participants were asked to choose how acceptable it was to sacrifice one individual from a number of different age groups in order to save five others in a trolley problem. The sacrificial targets were a 70‐year‐old male stranger, a 20‐year‐old male stranger, a 5‐year‐old male stranger, or a 20‐year‐old male disabled stranger. Our results indicated that more participants accepted sacrificing the elderly stranger than the other three targets; sacrificing the child was the least accepted option. These results indicate that the decision‐making process in a moral dilemma involves weighing others' lives according to their age and implicitly predicting their life span.